A Multicenter Observational Study on the Postoperative Outcomes of C3 Laminectomy in Cervical Double-door Laminoplasty. Issue 4 (May 2021) - Nakajima, Koji; Nakamoto, Hideki; Kato, So; Doi, Toru; Matsubayashi, Yoshitaka; Taniguchi, Yuki; Yoshida, Yuichi; Kawamura, Naohiro; Nakarai, Hiroyuki; Higashikawa, Akiro; Tozawa, Keiichiro; Takeshita, Yujiro; et al.
Abstract : Study Design: Multicenter retrospective observational study. Objective: To determine the differences between C3 laminectomy (LN) and C3 laminoplasty (LP) in cervical LP. Summary of Background Data: Interlaminar bony fusion after cervical LP is reported to be related to a decrease in postoperative range of motion (ROM) or neurological disorder. However, it remains uncertain whether C3 LN affects patient-reported outcomes, especially after double-door LPs. Therefore, this study aimed to investigate the effect of C3 LN compared with C3 LP in cervical double-door LP. Patients and Methods: Using our prospective database, consecutive patients with degenerative cervical myelopathy undergoing cervical double-door LP in 7 hospitals between April 2017 and May 2018 were enrolled. Before and 1 year after the surgeries, we collected the details of patient background data, operative factors, radiologic findings such as C2–C7 ROM angle and C2–C3 interlaminar bony fusion, the Japanese Orthopaedic Association (JOA) score, postoperative satisfaction, neck pain, and patient-reported outcomes such as Short Form-12 (SF-12), EuroQol 5 Dimension (EQ-5D), Neck Disability Index (NDI), and the Core Outcome Measures Index (COMI) for the neck. Results: In all, 152 patients were enrolled, including 97 undergoing C3 LP and 55 undergoing C3 LN. There were no significant differences in patient background data, complications, and operative factors. C2–C3 interlaminar bony fusion occurred more often in the C3 LP group (22.6% vs. 5.7%). There were also no differences in the C2–C7 angle, C2–C7 ROM angle, the JOA score, patient satisfaction, neck pain, SF-12, EQ-5D, NDI, and COMI between the groups. Conclusions: C2–C3 bony fusion after cervical double-door LP occurred more often in the C3 LP group than in the C3 LN group. C3 LN resulted in similar outcomes in complication rate, radiographic outcomes, and clinical outcomes compared with those of C3 LP. Level of Evidence: Level III.